Post-commencement adoptions. Issue 10 (2nd October 2021) - Harris, Alexandra Conroy
Abstract : Alexandra Conroy Harris, legal consultant at CoramBAAF, sets out the process to access information under 2005 adoption reforms as the first children adopted "post-commencement" reach adulthood